'Slum' Upgrading and 'Slum' Eradication under MDG Seven Target Eleven - Huchzermeyer, Marie (University of Rhodes. Sociology., 2008)
The modest MDG target on improving the lives of ‘slum’ dwellers occupies a complex and in some ways contradictory terrain. This chapter reviews the usage of the term ‘slum’ and its adoption into the Millennium Development Project. The slogan ‘Cities Without Slums’, which accompanies the target, has led to an initially unintended emphasis in official communication of the target. In order to explore the deviation between the norm that cities should not have ‘slums’ and the actual MDG target, the chapter reviews the role of norms and targets within the UN. Turning in more detail to MDG Seven Target Eleven, it compares the origin of Target Eleven with the trajectory that led to the adoption of the other MDG targets. Due to the World Bank’s role in the formulation of Target Eleven and its slogan, the chapter reviews World Bank urban policy at the time, as well as the World Bank’s subsequent shift to more directly embracing the urban poor and promoting informal settlement upgrading. The position of the urban economy and urban competitiveness within the World Bank’s policy of 2000 is relevant to understanding the coining of the slogan ‘Cities Without Slums’, as well as its utility to city beautification initiatives driven by the urban competitiveness agenda. The World Bank’s subsequent refinement in urban policy is not paralleled in high level
Draft chapter, forthcoming in Langford, M., Sumner, A. and Yamin, A. (eds). Millennium Development Goals and Rights: Past, Present and Future. Full book manuscript under review by Cambridge University Press.
Keywords: Slum upgradinf, slum eradication, South Africa Housing, MDG targets.